PARG-deficient tumor cells have an increased dependence on EXO1/FEN1-mediated DNA repair - Andronikou, Christina; Burdova, Kamila; Dibitetto, Diego; Lieftink, Cor; Malzer, Elke; Kuiken, Hendrik J; Gogola, Ewa; Ray Chaudhuri, Arnab; Beijersbergen, Roderick L; Hanzlikova, Hana; Jonkers, Jos; Rottenberg, Sven (The EMBO journal, 2024)
Targeting poly(ADP-ribose) glycohydrolase (PARG) is currently explored as a therapeutic approach to treat various cancer types, but we have a poor understanding of the specific genetic vulnerabilities that would make cancer cells susceptible to such a tailored therapy. Moreover, the identification of such vulnerabilities is of interest for targeting BRCA2;p53-deficient tumors that have acquired resistance to poly(ADP-ribose) polymerase inhibitors (PARPi) through loss of PARG expression. Here, by performing whole-genome CRISPR/Cas9 drop-out screens, we identify various genes involved in DNA repair to be essential for the survival of PARG;BRCA2;p53-deficient cells. In particular, our findings reveal EXO1 and FEN1 as major synthetic lethal interactors of PARG loss. We provide evidence for compromised replication fork progression, DNA single-strand break repair, and Okazaki fragment processing in PARG;BRCA2;p53-deficient cells, alterations that exacerbate the effects of EXO1/FEN1 inhibition and become lethal in this context. Since this sensitivity is dependent on BRCA2 defects, we propose to target EXO1/FEN1 in PARPi-resistant tumors that have lost PARG activity. Moreover, EXO1/FEN1 targeting may be a useful strategy for enhancing the effect of PARG inhibitors in homologous recombination-deficient tumors. Synopsis Targeting poly(ADP-ribose) glycohydrolase (PARG) is being explored as anti-cancer therapeutic strategy, and PARG loss may also contribute to resistance to PARP inhibitor (PARPi) treatment. This study provides insights into specific vulnerabilities that can render homologous-recombination (HR)-deficient tumors susceptible to the loss of PARG activity. Impaired de-PARylation in PARG-deficient cells affects the repair of single-strand breaks (SSBs) and processing of unligated Okazaki fragments. Genome-wide CRISPR/Cas9 screens reveal EXO1 and FEN1 as critical factors in cells deficient for PARG and BRCA2. Inhibition of EXO1/FEN1 in PARG;BRCA2-deficient cells results in unresolved Okazaki fragments, which persist as single-strand DNA (ssDNA) gaps. Persistent ssDNA gaps become specifically lethal to HR-deficient cells when converted into double-strand breaks (DSBs) upon replication. Genome-wide loss-of-function screens reveal DNA repair genes essential in HR-defective cells lacking PARG, suggesting ways for therapeutically exploiting PARG inhibitors and targeting PARPi-resistant tumors.